PERNIKAHAN SIRRI DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Muksalmina Muksalmina (Jurnal Inovasi Penelitian, 2020)
Marriage is the necessity of every human being in fulfilling the needs of his life as a social creature. Because the issue of marriage is an important affair to maintain the benefit of the whole community, then the State has the right to regulate this business in the form of clear rules with the aim to provide protection of law and order in the life of society. This study examines the legal aspects of marriage that occur in the community i.e. the marriage of Sirri. The marriage is lawful or not in the view of Islamic law and the positive law that often becomes a polemic in society causes a negative impact on the parties involved both husband, wife and child. The results of this research, can be concluded that the marriage of Sirri is valid either by Islamic law or positive law, but in the view of the Islamic law of marriage is unlawful.